Análise dos determinantes reais do mercado de fundos de pensão nos estados brasileiros - Alves, Jacqueline Lima (2005)
The problem of the population aging, among others aspects, has taken a lot of countries, including Brazil, to rethink its pension systems. Inevitably, the discutions lead to the pension funds, either publics or privates. The purpouse of this study is to evaluate the size of the market of pension fund in the Federative Units of Brazil. This study was done using variables that could explain the size of the market, such as education (EDU25), the percentage of the population over 65 years (PP65), that it searchs to catch the influence of the population aging in the development of the private pensions funds; the amount of participants (PFP) and pensioners (PAFP) that they are sector parts and its respective dependents (DFP). The variable sample used for the econometrical calculations, referring to the period from 1996 to 2000, the Federative Units of Brazil, with exception of the North Regions States for the difficult to get the relative data the population above of the 65 years and the Federal District for presenting big variations of the variable in comparison to the others of the sample, resulted in 95 comments. The empirical inquiry was lead through regression analysis with data in panel, esteem for GLS (Generalized Minimums Squared) method, considering TIF/PIB (Totals investments of the Pension funds as proportion ratio of the GDP) as changeable dependent and PP65, EDU25, PFP, PAFP, DFP, as changeable independent. The results for each one of the independent variable indicate that all are statistics significant, for the level of significance 0,10, as well as the signals corroborate the first hypotheses, with exception of DFP variable. Althought, the probability of rejection of the true hypothesis is very low for the model variable. It concludes that the existence of the problem of the aged one, explains the growth of the pension funds. Moreover, the higher level of education and a biggest continent enclosed by the pension funds, will contribute decisively for the development of the sector in the Federative Units of Brazil.